Pulmonary Alveolar Microlithiasis: An Isolated Case in a Hispanic Male - Preethi Dileep Menon; Sarah Hackman (Hindawi Limited, 2020)
Pulmonary alveolar microlithiasis (PAM) is an uncommon hereditary lung disease characterized by widespread deposition of calcium phosphate microliths within the alveolar spaces. It is considered an autosomal recessive disease with a mutation in a gene encoding a sodium phosphate cotransporter. The imaging findings in the early phase of disease can be mistaken for miliary tuberculosis or sarcoidosis. However, the classic radiologic findings in the later phases of disease show numerous opacities causing a "snowstorm" appearance to the lungs that corresponds with widespread deposition of microliths throughout the lung parenchyma. Although the disease often progresses over a slow time course, there are no effective therapies, and bilateral lung transplantation is recommended when there are increasing oxygen requirements or evidence of pulmonary hypertension.